Egyptology from the First World War to the Third Reich : ideology, scholarship, and individual biographies - Schneider, Thomas, 1964-; Raulwing, Peter. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2013, ISBN: 9789004248649., 2013)
Only recently has Egyptology begun to critically examine its history in the first half of the 20th century. This book presents major contributions that analyze the interplay of personal biographies and political history, ideologies and academic scholarship between the First World War and the Third Reich. Peter Raulwing and Thomas Gertzen study the political activism of Friedrich Wilhelm Freiherr von Bissing, professor of Egyptology at the University of Munich and art collector, during and after the First World War. Thomas Schneider's contribution is the first comprehensive treatment of the biographies of German and Austrian Egyptologists in the time of National Socialism and their careers after 1945, with remarks on the relationship between Egyptological scholarship and Nazi ideology. Lindsay Ambridge analyzes the scholarship of James Henry Breasted, the patron of North American Egyptology, in the context of racial ideologies of the early 20th century. A concluding chapter by Peter Raulwing, added after the death of Manfred Mayrhofer, patron of the study of Indo-Aryans in the Ancient Near East, reflects on the 20th century ideological and academic interest in the question of Indo-Aryans in the Ancient Near East. In the introductory chapter, Edmund Meltzer places these studies and their significance in the wider context of Egyptological and historiographical scholarship. \'...this book makes a significant contribution to exploring a dark chapter in Egyptology's history as a discipline and an important step in understanding the effect that period had on the academic community.\' Edward Mushett Cole, University of Birmingham